2018
DOI: 10.1128/mspheredirect.00238-18
|View full text |Cite
|
Sign up to set email alerts
|

Genes Activated by Vibrio cholerae upon Exposure to Caenorhabditis elegans Reveal the Mannose-Sensitive Hemagglutinin To Be Essential for Colonization

Abstract: The waterborne diarrheal disease cholera is caused by the bacterium Vibrio cholerae. The facultative human pathogen persists as a natural inhabitant in the aquatic ecosystem between outbreaks. In contrast to the human host, V. cholerae requires a different set of genes to survive in this hostile environment. For example, predatory micrograzers are commonly found in the aquatic environment and use bacteria as a nutrient source, but knowledge of the interaction between bacterivorous grazers and V. cholerae is li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Interestingly, the Msh pilus has been shown to play a role in a number of other host-microbe systems. For instance, within the Vibrio genus, Msh pili have been suggested to be important for adherence to human intestinal cells ( 33 ), as well as colonization of the digestive tract of Caenorhabditis elegans ( 34 ), and the light organ of Euprymna tasmanica ( 35 ). In addition, in both Vibrio and Pseudomonas systems, evidence suggests this pilus can interact with components of the mammalian immune system ( 12 , 36 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the Msh pilus has been shown to play a role in a number of other host-microbe systems. For instance, within the Vibrio genus, Msh pili have been suggested to be important for adherence to human intestinal cells ( 33 ), as well as colonization of the digestive tract of Caenorhabditis elegans ( 34 ), and the light organ of Euprymna tasmanica ( 35 ). In addition, in both Vibrio and Pseudomonas systems, evidence suggests this pilus can interact with components of the mammalian immune system ( 12 , 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…Each point represents the competitive index measured for a single biological replicate. (33), as well as colonization of the digestive tract of Caenorhabditis elegans (34), and the light organ of Euprymna tasmanica (35). In addition, in both Vibrio and Pseudomonas systems, evidence suggests this pilus can interact with components of the mammalian immune system (12,36).…”
Section: Figmentioning
confidence: 99%
“…13 Previous studies have revealed virulence-associated factors involved in the pathogenicity of V. cholerae, including zonula occludens toxin (zot), accessory cholera enterotoxin (ace), El Tor hemolysin (hlyA), hemagglutinin protease (hapA), RTX toxin (rtxCABD), thermolabile hemolysin (tlh), mannose-sensitive hemagglutination (MSHA; mshA), and putative type IV pilus ( pilA). [14][15][16][17][18] Therefore, continuous detection of the non-O1/ 0139 V. cholerae in aquatic products is also crucial for food safety systems.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the msh pilus has been shown to play a role in a number of other host-microbe systems. For instance, within the Vibrio genus, msh pili have been suggested to be important for adherence to human intestinal cells [33], as well as colonization of the digestive tract of Caenorhabditis elegans [34], and the light organ of Euprymna tasmanica [35]. Additionally, in both Vibrio and Pseudomonas systems, evidence suggests this pilus can interact with components of the mammalian immune system [12, 36].…”
Section: Resultsmentioning
confidence: 99%